Sustainability of Crop Residues and Manure Management in Smallholder Cereal-Legume-Livestock Systems in the Savannas of West Africa - Opoku, Andrews (2015)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements of the degree of DOCTOR OF PHILOSOPHY In Soil Science,